Who Is Keeping Their Unused Opioids and Why?. Issue 1 (21st March 2019) - Neill, Luke A; Kim, Howard S; Cameron, Kenzie A; Lank, Patrick M; Patel, Deesha A; Hur, Scott I; Opsasnick, Lauren A; Curtis, Laura M; Eifler, Morgan R; Courtney, D Mark; Wolf, Michael S; McCarthy, Danielle M
Abstract: Objective: To better understand patients' reasoning for keeping unused opioid pills. Methods: As part of a larger study, patients were asked their plans for their unused opioids. Responses were categorized as "dispose, " "keep, " and "don't know." Baseline characteristics were compared between the "keep" and "dispose" groups. Verbatim responses categorized as "keep" were analyzed qualitatively using a team-based inductive approach with constant comparison across cases. Results: One hundred patients planned to dispose of their pills; 117 planned to keep them. There were no differences in demographics between the groups. Among patients who planned to keep their pills, the mean age was 43 years and 47% were male. Analysis revealed four categories of patient responses: 1) plans to keep their pills "just in case, " with reference to a medical condition (e.g., kidney stone); 2) plans to keep pills "just in case" without reference to any medical condition; 3) plans to dispose in delayed fashion (e.g., after pill expiration) or unsure of how to dispose; and 4) no identified plans, yet intended to keep pills. In this sample, there were no differences in characteristics of those reporting planning to keep vs dispose of pills; however, there were diverse reasons for keeping opioids. Conclusions: This manuscript describes a sample of patients who kept their unused opioids and presents qualitative data detailing their personal reasoning for keeping the unused pills. Awareness of the range of motivations underpinning this behavior may inform the development of tailored education and risk communication messages to improve opioid disposal.